AB1152 Early Intervention in Musculoskeletal Disease Can Reduce Temporary Work Disability. (9th June 2015) - Vela, P.; Abasolo, L.; Lajas, C.; Gil, S.; Cuenca, N.; Senabre, J.M.; Lopez, A.; Barros, A.; Macia, C.; Tejon, P.; Aparicio, M.; Rosas, J.; et al.
Abstract : Background: Musculoskeletal diseases (MD) cause in Spain 24% of temporary work disability (TD) and 50% of permanent (PD). A study of early intervention (assessment and immediate treatment by a rheumatologist) reduced TD days (39%) and evolution to PD (50%) (1). Using the "Fit for Work" European coalition, led by the Abbvie Foundation, the program is implemented nationwide. Objectives: Describe and evaluate the effectiveness of MD-TD (1) program in various public health areas. Methods: Non-randomized intervention study, patients initiating MD-TD. Intervention group (IG): MD-TD program (1); Control group (CG): usual care (primary care). Primary endpoint: mean and median TD duration. Secondary: program duration, age, sex, diagnosis, date of rheumatologist's first visit, rheumatologist discharge date proposal. Statistical analysis: descriptive. Program relative effectiveness (RE) compared with usual care = (average duration CG- average duration IG)/average duration CG * 100. Results: The program has been implemented in seven autonomous communities. In 6 centres (924 patients), the program median duration was 13 months (8-23). The most frequent causes of TD were tendinitis (23.5%), sciatica (20.68%), back pain (20.27%) and cervical pain (8%). TD median days since the rheumatologist's first visit until the proposed discharge is similar in all centres (19 days, 8-47). The delay from the start of TD to the rheumatologist's first visit varies considerably between centres from 7 days (4-11) in the best case, to 32 (18-50) at worst. There are also differences in the time since the rheumatologist indicates discharge until it occurs, from 0 days in the centre where the own rheumatologist emits discharge, to 17 (4-80) in the worst case. Alicante Hospital is the only with data of control population given by inspection. 261 episodes were analyzed. The TD average was 46.8 days in IG, and 92 days in CG, which is a program RE of 49%. Delay to rheumatologist's first visit was 7 days (4-11), and to discharge 0 days (rheumatologist himself gives discharge). Days off work according to diagnosis were: low back pain IG 30.68 days, CG 53 days, RE 42%; joint disorders IG 19.55 days, CG 75.4 days, RE 74%; neck pain GIG 46.15 days, CG 62.2 days, 25.8% RE; tendinitis IG 51.2 days, CG 84.5 days, 39.4% RE; sciatica IG 58.25 days, GC 136.59 days, RE 57.3%; osteoarthritis IG 66.72 days, CG 141.6 days, 52.8% RE. Conclusions: Early intervention in musculoskeletal pathology reduces days off work significantly. The most benefited conditions were tendon and joint disorders, and sciatica. Success depends on the rapid referral of the patient, centralizing medical and administrative responsibilities in the Rheumatologist. References: Abásolo L et al. A health system program to reduce work disability related to musculoskeletal disorders. Ann Intern Med. 2005 Sep 20;143 (6):404-14. Acknowledgements: This study was funded by the Abbvie Foundation, which was not involved in the analysis or in drafting the manuscript. Disclosure of Interest: None declared